Long-term outcomes in children with and without cleft palate treated with tympanostomy for otitis media with effusion before the age of 2 years. (1st December 2020) - Inoue, Maki; Hirama, Mariko; Kobayashi, Shinji; Ogahara, Noboru; Takahashi, Masahiro; Oridate, Nobuhiko
Abstract: Background: Long-term outcomes of children with and without cleft palate receiving early treatment for otitis media with effusion (OME) are unclear. Objectives: To compare long-term otological and audiological outcomes between children with and without cleft palate treated with tympanostomy for OME before the age of 2 years. Material and methods: Ninety-five children (180 ears) with cleft palate (study group) and 97 children (185 ears) without (control group) were followed-up to a maximum age of 7 years. We retrospectively analyzed the audiological outcomes at the age of 7 years, and the otological outcomes at the last examination. Results: The percentages of children with OME resolution before the age of 7 years were 47.4% and 60% in the study and control groups, respectively, and those of ears with healed tympanic membrane were 71.7% and 79.5% in the corresponding groups. Significantly more ears were subjected to retympanostomy in the study (31.1%) than in the control group (21.6%). Mean pure-tone average (0.5‒4 kHz) was 15.6 dB HL and 14.3 dB HL for the corresponding groups. Conclusions/significance: Otological and audiological outcomes in both groups were similar. The audiological prognosis was favorable regardless of the cleft palate condition.